ANTI-INFLAMMATORY AND ANALGESIC PROPERTIES OF CARALLUMA FIMBRIATA: A COMPREHENSIVE STUDY - Indu Saini; Kokkula Pavan Kumar; K. Ashok Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
This comprehensive preclinical investigation explores the anti-inflammatory, analgesic, and anxiolytic properties of Caralluma fimbriata extract using validated animal models. The study systematically examines the therapeutic potential of the methanolic extract administered at two graded doses—100 mg/kg and 200 mg/kg—benchmarking its effects against standard pharmacological agents known for their efficacy in each respective domain. To evaluate the anti-inflammatory efficacy, the carrageenan-induced paw edema model was employed, while nociceptive response was measured using the hot plate test. Additionally, the elevated plus-maze paradigm was utilized to assess the anxiolytic profile of the extract. The results indicate that Caralluma fimbriata exhibits pronounced, dose-dependent anti-inflammatory activity, as evidenced by significant attenuation of paw swelling. Concurrently, the extract elicited notable antinociceptive effects, suggesting its potential utility in pain management. Furthermore, behavioral analyses revealed a substantial reduction in anxiety-like symptoms, highlighting its anxiolytic capacity. Phytochemical screening of the extract revealed a rich repertoire of bioactive constituents, prominently including pregnane glycosides, flavonoids, saponins, and phenolic compounds. These phytoconstituents are believed to act synergistically through multiple pharmacodynamic pathways, including the inhibition of cyclooxygenase enzymes, modulation of inflammatory mediators, suppression of oxidative stress, and interaction with central neurotransmitter systems. Collectively, the findings of this study underscore the potential of Caralluma fimbriata as a multifaceted natural therapeutic agent. Its ability to alleviate inflammation, mitigate pain, and reduce anxiety symptoms presents a compelling case for its further development as a phytopharmaceutical intervention. Given its traditional use and favorable preliminary safety profile, Caralluma fimbriata may offer a promising alternative or adjunct to conventional therapies for managing inflammatory disorders, nociceptive pain, and anxiety-related conditions.